2003
DOI: 10.1007/s00261-001-0157-x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of tissue harmonic imaging in the evaluation of abdominal and pelvic lesions

Abstract: THI improved overall image quality and lesion characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
1
18
0
1
Order By: Relevance
“…Although a comparison of conventional sonography with THI and SCI was beyond the scope of this study, better diagnostic performance has been shown in a variety of abdominal and pelvic organs with the use of THI or SCI in comparison with standard B-mode sonography because of improved lateral resolution and elimination of unwanted artifacts. [9][10][11] In addition, the combination of SCI and THI helps reduce specific limitations of each algorithm (eg, blurring and decreased posterior echo characteristics on SCI sonography and decreased penetration in THI). 12 However, a perfect overlap between the two diagnostic methods did not occur for the size and number of lesions in that sonography tended to miss the smallest lesions (<5 mm), to overestimate the lesion size, and to underestimate number of lesions when compared with cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a comparison of conventional sonography with THI and SCI was beyond the scope of this study, better diagnostic performance has been shown in a variety of abdominal and pelvic organs with the use of THI or SCI in comparison with standard B-mode sonography because of improved lateral resolution and elimination of unwanted artifacts. [9][10][11] In addition, the combination of SCI and THI helps reduce specific limitations of each algorithm (eg, blurring and decreased posterior echo characteristics on SCI sonography and decreased penetration in THI). 12 However, a perfect overlap between the two diagnostic methods did not occur for the size and number of lesions in that sonography tended to miss the smallest lesions (<5 mm), to overestimate the lesion size, and to underestimate number of lesions when compared with cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…No examination was conducted in the conventional B-mode, so no attempt was made to compare results with and without THI and SCI on the assumption that the superiority of these algorithms in terms of improvements in image quality versus conventional sonography has been widely validated in the radiology literature. [9][10][11][12] By generating an image from multiple scanning lines, SCI improves depiction of lesion margins, reduces image artifacts (such as speckling, clutter, acoustic shadowing, and acoustic enhancement), and enhances image contrast; similarly, THI tends to abolish most artifacts that degrade conventional sonograms. In addition, our choice reflected the availability of sonographic machines equipped with THI and SCI at our institution.…”
Section: Sonographymentioning
confidence: 99%
See 1 more Smart Citation
“…THI and SCI) which substantially improve image quality and diagnostic yield in comparison to conventional US [23,24]; a consensus obtained between the two operators as to technical modalities of carrying out US examination of the urinary bladder; preliminary discussion of most frequently encountered pitfalls in bladder US diagnostics. On clinical grounds, this implies that well-trained and motivated operators independently of their experience may achieve high diagnostic capabilities in identifying FBWA.…”
Section: Discussionmentioning
confidence: 99%
“…The improved image quality of THS has led to its widespread use in evaluation of the abdomen (liver, kidney, gall bladder, bile ducts), vessels and breasts [7][8][9][17][18][19][20][21][22][23][24][25][26][27]. Limitations of THS include overall coarse echo texture and decreased penetration [17,18].…”
Section: Introductionmentioning
confidence: 99%